Metamorphosis as a process: architectures of common spaces | Dimitris Gourdoukis | TEDxPatras (TEDx Patras, 2022)
: ΠΡΑΥ ΣΥΝΟΣ, ΕΛΥΣΤΗΜΑΣ, ΕΛΥΣΤΗΜΑΣ. ΠΡΑΥΣΤΗΜΑΣ, ΕΛΥΣΤΗΜΑΣ. ΚΑΙ ΚΑΙ ΤΟΝ ΓΙΑΖΕΣ, ΕΛΥΣΤΗΜΑΣ, ΕΛΥΣΤΗΜΑΣ Καλημέρα! Το μοναδικό μου είναι για το κοντέ του μεταμορφωτήσης, Επίσης, νομίζω ότι είναι ένα concept εύκολο να καταλάβεις στον πρώτο βαθμό, γιατί η αρχιτεκτονία το κάνει. Μπορεί να αλλάξει χώρο. Μπορείς να έχεις έναν παλαιό κτήριο, μπορείς να το εξελίξεις και να το κάνεις σε κάτι νέο. Μπορείς να δημιουργήσεις έναν νέο κτήριο και να αλλάξεις μια ολόκληρη περιοχή. Ή μπορείς να δημιουργήσεις ένα δημιουργικό κτήριο και να αλλάξεις τη ζωή μιας ολόκληρης πόλης. Αλλά, σε αυτό το μορφό, δεν είμαι ενδιαφέρον σε αυτήν την εξελίξη. Είμαι ενδιαφέρον στην ιδέα να δημιουργήσω χώρες που μπορούν να είναι σε μια συνεχή στιγμή εξελίξης. Άλλης, πώς μπορούμε να δημιουργήσουμε χώρες που πάντα γίνονται σε κάτι άλλο. Θα εξηγήσω αυτό μέσα σε ένα συγκεκριμένο παράδειγμα, που θα σας δείξω. Αλλά, πριν να πάω σε αυτό, θα ήθελα να δημιουργήσω το πρότυπο μέσα στο οποίο πρέπει να δουλεύουμε σήμερα. Αυτό είναι το πρότυπο που μας έφερε από την κρίση του COVID-19. Λοιπόν, μπορούμε να δημιουργήσουμε, ίσως, αυτό το πρότυπο με αυτό το όνομα, την πρωτοπολιτική κατάσταση. Αυτό, φυσικά, δεν είναι ένα νέο concept. Είναι ένα μικρό concept που προσπαθεί να δημιουργήσει τις παθολογικές, τις κοινωνικές παθολογικές που παρακολουθούν τις κοινωνικές. What COVID-19 did was to take those problems, intensify them, and make them painfully obvious in our everyday life. So, we can somehow codify those issues, those social pathologies, in four sentences, to simplify things. So, the first is the rapid explosion of inequalities, which means that rich people are getting richer, poor people are getting poorer, the gaps between the different classes are getting larger and larger. The second is a deficit of democracy through the weakening of democratic processes. And that means that democracy all over the world is in serious problem. It's having serious issues to function properly, and that includes the Western world, where we think that democracy is a given, where it's not. Then, we have the inability to socialize and form collectives. That means that people find it hard to come together and do things together, and they find it even harder to develop political action together. And then, there is a general sense of reaching a dead end, especially for young people, a sense of you cannot even think of what you can do in order to change those things. And remember, we are talking about architecture, and architecture, if we want to be honest, cannot solve those problems. Design cannot solve those problems. It tried to do so in the past, and it failed. However, architecture is not only about solving problems. That's how we used to think about architecture, but we can also think about designing as a way to create possibilities. That changes a little bit the way we see things, because we can create spaces with the possibilities to enable action that will do something to address those issues. Because those issues do have an impact on space, and we can see them in our cities. We can see the reflection of all those problems that we are facing in urban space, and we see them mainly as a lack of public space and urban ecology, where public space is the space that is open to all people inside the city, and urban ecology is the understanding that the city is a system. So it's not just about more green space, or more bicycle lanes, or beautiful buildings. It's about understanding that the city is a whole, and everything is linked to everything else. So we need to address those issues, and we need to do something about this situation, obviously. And in order to do that, we have to rethink again the tools that we use to understand the cities and space. And those are two concepts that we regularly use. We understand space as public or private, where public space is space that is open to everybody. Access is allowed to all people. And then private space is, of course, space that access is somehow limited to some people. I think that in order to move forward today, we need a third term, and that's the idea of common space. Now, common space is closer to public space, only that it's far more radical in the way that it understands ownership. Public space, or a space, becomes common when people occupy it. They make it their own without exclusions in terms of how it can be used and how decisions are made for that space. And it is exactly in this condition, when space has become common, that this idea that I talked about, a space that is in constant state of metamorphosis, a space that is always changing, can be created through the people that occupy it and do things there. Socialize, organize, connect, develop political thinking and political action. So I'm going to move forward with the example that I mentioned, which is actually a recent project we did for a Banton factory here in Patras. It was an ideas competition that was asking for any idea of what can happen into this Banton factory. This is an older photo of the building complex. This is more or less the state that you can find it today. As you can see, it's rather large. You have many buildings in there, abandoned. Some of them are in ruins. And it's inside the city or on the edge of the city. So when we started thinking about how we can actually start designing something in there and having in mind everything that I told you in the beginning, we realized that no matter how much we want to create those common spaces in cities, modern cities and especially Greek modern cities, they don't have much space left. So situations like this, large abandoned factories inside the city, might be their last chance or something like that. So having that in mind, we decided that that's what we want to do. We want to try and create in that space, public space that will have the ability, will give the possibility after people occupied it to become common. And in order to do that, we decided that we have to bring in there many different things and mix them together. So we decided that we created six categories of architectural elements. We call them typologies that we decided we are going to install in there. And of course in the hope that they are going to start interacting with each other. So the first typology, we call it the ruin, which might sound a little bit strange for an architectural element that you design. However, it refers to the way that we propose to deal with the existing building stock. So we say that all the buildings that are in a relatively good shape, we renovate them. The ones that are in ruins, we keep them as such. We keep the ruins and we install in there new functions. For example, on this Siemens on the upper part, you can see all the buildings that are without roofs. We propose inside them courts, gardens, playgrounds, etc. So the ruins somehow become the background for what's happening in there. And at the same time, they form a kind of collective memory of the city and for what it used to be there. Also a sense of economy of material by using what you already have. The second typology or type of architectural element is that of the forum, which of course is maybe the most important for us because this is exactly the place where we tend people to come together. So those are large open spaces that people can socialize. And they have a double existence. There is a large one which is inside. It's actually the largest building of the complex, which is empty in order to become that open space. You can see it here in the middle. And then all around you have stores, offices, workshops, working places, in general things that will bring people there. And then this space is the place of interaction. And then we also have a similar space on the outside, which is much closer to what we normally understand as public space. It's an open space for people to meet. Then the third typology is that of the street. And the street is what's around and between all the other elements. It connects them. And usually when we are in the city, we go out from a building in order to enter the street. In our case, the streets are also penetrating the buildings. So they are going through the existing buildings in order to better connect the different elements that we find there. The fourth element or typology is that of the agora. And that's the financial aspect of the proposal. So again, we use one of the existing cells of existing buildings to create a large market. But also we propose many different stores, restaurants, etc. dispersed all around the area of the site. The fifth typology is that of the garden, which is a little different to the four previous ones because all four previous ones are things that we are used to find inside the city. They are urban elements. The garden, on the other hand, is more a representation of nature. So in that sense, it's like a counterpoint to the other four. Therefore, we have many gardens, smaller and larger ones in the proposals, that are found, again, dispersed all around the area of the site. And in many cases, they act as a surprise. For example, you can walk out of the pool that you can see in the lower side of the image, and you enter a space like this, which is a closed, hidden garden inside the building. And this is a diagram that shows all the different gardens that are positioned within the structure. And finally, we have the last type, let's say a space, that we propose. We call them the personal spaces, which exactly says that it's not always about coming together. Inside such a structure, we need to have smaller places that are generic enough for people to occupy them and express their own individuality. So we have those six types, those six architectural elements, and in order to support them, of course, we need a very rich and extensive program, different kinds of functions that will be inside there. So we propose for the structure things like a large pool or a theater or working spaces, offices, places where you can rent, places where people can rent as groups, and a market you can see here, or the pool or the workshops. Here, this is an image that shows that all those places are actually next to each other, and you can walk, for example, from the pool then to the market that's next to it, and then to the theater that's on the other side. And of course, open spaces on the outside, the theater, and a section of the forum, the large public space in the middle of the proposal, or sports places outside. So in a sense, I think that the idea behind this project is quite simple, is that you bring together many different things on the side, and you position them strategically, and that brings people there. And then, around them and in between them, you create many open spaces for people to occupy them and start to interact, start coming together, start discussing, and maybe start forming political conscience and political action. And in a sense, that's what we think about design, what design should do, at least on the level of the city. It needs to create those common spaces. It needs to create possibilities for people to meet and come together and find solutions by themselves to those serious issues that we are facing today as a society. And as I said at the beginning, that's ultimately the only way to make spaces that do that, that are in a constant state of metamorphosis, that are always becoming something else. That can happen only when people occupy the space, interact with each other, socialize, and then finally develop political action when they come together. Thank you. .